ASOSIASI PENYAKIT ALERGI ATOPI ANAK DENGAN ATOPI ORANG TUA DAN FAKTOR LINGKUNGAN - Syaiful Ludfi, Achmad; Agustina, Luki; D, Fetarayani; A, Baskoro; S, Gatot; Effendi, Chairul (journal of internal medicine; Vol. 13, No. 1 Januari 2012, 2014)
Atopic allergic disease related with genetic factor and environment. Some studies found parents and environment factor have an important role on emerging of clinical manifestation. This study try to evaluated wheather atopic parents and environment can inuanced clinical manifestation of allergic disease in their children. This information is important for education and in intervention of treatment for patients with allergic disease. This study is an observasional analytic case control study involved all student range from junior until high school level and their parents at Surabaya region. Data was taken by quisioner, physical and Skin Prick Test (SPT). Statistical analyses using multivariat logistic regression test. Threehundreed forthy eight student was enrolled where 91 (26.1%) with positive SPT have atopic father 26 (56.9%) and atopic mother 25 (54.3%) on the other hand 249 student with negative SPT have atopic father 22 (43.1%) and atopic mother 21 (45.7%). Logistic regression test found that sequency number of birth and explanation dust mate assosiated with occurence of clinical manifestation of atopic allergic disease in children.
Keywords: Atopic allergic, children, parents, dust mite